BREAST CANCER CHEMOTHERAPY RESPONSE IN WAHIDIN SUDIROHUSODO HOSPITAL, MAKASSAR - Prihantono Prihantono; Haryasena Haryasena; Daniel Sampepajung (Nusantara Medical Science Journal, 2016)
ABSTRACTIntroduction: Treatments of breast cancer are multidisciplinary. Chemotherapy isone of the most important modalities and has become the standard of breast cancertreatment of in the adjuvant or neoadjuvant setting. Evaluation is needed in order tounderstand the effectivity of the chemotherapy regiment, to improve the servicesystem and to share with other centers. Objectives: to understand thecharacteristics of chemotherapy patients, types of regimen, settings chemotherapyand neoadjuvant chemotherapy response of breast cancer. Methods: Aretrospective study was done by reviewing the administrative data of cancer patientswho were treated in the surgical oncology Wahidin Sudirohusodo Hospital, Makassarin 2014. Results: During 2014 has been carried out chemotherapy for 247 breastcancer patients, used as neoadjuvan setting 145 cases (59 %) and Adjuvan 102cases (41%). The regimen used are CAF 155 cases ( 63%), TAC 55 cases ( 22%), TA 20 cases (8%), GC 11 cases ( 5%), dan Vinoralbine 6 cases (2%).Cumulative Clinical Response are: complete response 3 cases (2%), partialresponse 112 cases (78%), stable disease 23 cases (15%), and progresive disease9 (5%). Chemoterapy response by subtype: Luminal 67%, Her2 70%, Triple Negatif88%. Conclusions: Breast cancer clinical response to various chemotherapyregimens are good, regimen and subtype affect the response to chemotherapy.Keywords: breast cancer, chemotherapy, clinical response